Determinante do voto partidário: uma análise do voto em eleições para o Executivo no Estado de São Paulo – 1998-2006 - Tavoni, Fabrizio Martins (Universidade Federal de São Carlos, 2009)
The objective of this work is to analyze the partisan vote in elections for the Executive in the State of São Paulo, as much with the vote for Governor how much for President. The clipping that was made for this work is the period that understands the elections of 1998, 2002 and 2006, being that the analyzed parties are: PSDB (Brazilian Social democracy Party) and PT (Labor Party). The studied data had been collected in TSE (Electoral Superior Court) e, from them, made crossings between candidate the President for a party and candidate the Governor for the other party and vice versa, in order to observe the coherence of the vote in the parties in distinct disputes. From this maps of the vote in the State was made, having shown where each party gets better resulted and also to verify if in such a way in the dispute for the government of the State how much for the Presidency it has coherence in the partisan vote.
Keywords: Processos políticos; Comportamento eleitoral; Voto São Paulo (Estado); Partidos políticos; Geoprocessamento do voto; Coerência do voto; Dicotomia partidária; Electoral behavior; Maps of the vote; Coherence of the vote; Political parties; Partisan dichotomy; CIENCIAS HUMANAS::CIENCIA POLITICA